2022
DOI: 10.1155/2022/5967078
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget and Multipathway Regulation of Zhenqi Fuzheng Granule against Non-Small Cell Lung Cancer Based On Network Pharmacology and Molecular Docking

Abstract: Background and Objective. The morbidity and mortality rates of non-small cell lung cancer (NSCLC) remain high. Zhenqi Fuzheng (ZQFZ) granule, which consists of Astragali Radix and Ligustri Lucidi Fructus, is commonly used to improve the immunity of cancer patients. However, the mechanism of ZQFZ granule against NSCLC is still unclear. In this study, the network pharmacology and molecular docking approaches were used to investigate the potential mechanism of ZQFZ granule on NSCLC. Methods. The ingredients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…It is also possible for certain compounds to be more beneficial in their anticancer mode of action, although there is still a distinctive lack of research in this area to evaluate this statement. Such results strongly corelate with in vivo studies, where multiple plant-derived substances were found to have an anticancer and chemopreventive mode of action based on a variety of different mechanisms, including antioxidant, anti-inflammatory, induction of apoptosis, detoxification, cellular damage prevention, inhibition of cell proliferation, inhibition of cell cycle progression, inhibition of cell invasion, migration, and adhesion, and stimulation of the immune function [3][4][5][6][7][8][9][17][18][19][20][21][22][38][39][40][41][42][43][44][45][46][47][48][49]78,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120]124,[134][135]<...…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is also possible for certain compounds to be more beneficial in their anticancer mode of action, although there is still a distinctive lack of research in this area to evaluate this statement. Such results strongly corelate with in vivo studies, where multiple plant-derived substances were found to have an anticancer and chemopreventive mode of action based on a variety of different mechanisms, including antioxidant, anti-inflammatory, induction of apoptosis, detoxification, cellular damage prevention, inhibition of cell proliferation, inhibition of cell cycle progression, inhibition of cell invasion, migration, and adhesion, and stimulation of the immune function [3][4][5][6][7][8][9][17][18][19][20][21][22][38][39][40][41][42][43][44][45][46][47][48][49]78,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120]124,[134][135]<...…”
Section: Discussionsupporting
confidence: 64%
“…The study conducted by Duke University Medical Center showed that the use of a stable topical formulation of 15% L-ascorbic acid, 1% alpha-tocopherol, and 0.5% ferulic acid was particularly effective for reducing the thymine dimer mutations known to be associated with a skin cancer. However, the relatively small number of patients evaluated limited this study [116].…”
Section: Phenolic Acid In Skin Cancermentioning
confidence: 99%
“…As for safety, AS-IV is an active saponin isolated from Astragali Radix, which has been widely used in numerous TCM preparations, such as Qi-Shen-Yi-Qi pill, 103 Shen-Qi-Jiang-Tang granule 19 and Zhen-Qi-Fu-Zheng granule. 104 Thousands of years of clinical usage indicates a good safety. At present, although there is no systematic toxicology study, anecdotal studies show that AS-IV has no obvious toxicity or adverse reactions.…”
Section: Perspectivesmentioning
confidence: 99%
“…Molecular docking was carried out using Auto Dock Vina software (https://vina.scripps.edu/) to investigate the binding interaction between the components and the target site. After docking, the binding energy was used as a reference for screening the active compounds and the a nity ≤ -5.0 kJ/mol was used as the basis for screening the active ingredient targets of the "Astragalus-Ligustrum" drug pair [20].…”
Section: Molecular Docking Forecastsmentioning
confidence: 99%
“…Chinese patent medicine preparations of Ligustrum lucidum and Astragalus membranaceus as the main components (such as Zhenqi Fuzheng capsule, Zhenqi Fuzheng granule and Zhenqi Fuzheng dispersible tablet) have been widely used in combination chemotherapy for tumor treatment. [9] However, the speci c mechanism of their anti-cancer mechanism has not been fully elucidated, and because of the multi-component and multi-target integrated regulation of traditional Chinese medicine in treating diseases, the traditional monomer research mode can hardly re ect this feature of Chinese medicine in treating diseases. The development of modern bioinformatics and systems pharmacology elaborated the special synergistic interactions among the herbs of Chinese medicine formulations through a multi-target and multi-pathway approach.…”
Section: Introductionmentioning
confidence: 99%